Maternal anemia: a comprehensive study on fetomaternal consequences from menarche to menopause - Bhati, Bijal S.; Bajpai, Shubhendu; Patel, Mosam; Gori, Mehjbin; Panasara, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Anaemia stands out as the most prevalent haematological condition encountered during pregnancy. Anaemia poses significant risks to maternal health, contributing to higher rates of morbidity and mortality among pregnant individuals. This condition can be identified and managed during the antenatal phase, thereby averting the significant risks associated with anaemia in both pregnancy and labour. The present study was conducted to investigate the incidence of anaemia among pregnant patients and women of reproductive age. Methods: A prospective study was carried out at SMS Multispecialty Hospital and Dr. M. K. Shah Medical College and Research Centre. The study involved both indoor and outdoor patients from the obstetrics and gynaecology department, specifically those admitted for delivery at SMS Multispecialty Hospital. A total of 75 antenatal patients and 25 female patients from both reproductive and menopausal age groups were selected consecutively for this study. A comprehensive clinical history was gathered, encompassing the patient's complaints, socio-economic background, obstetric history, menstrual history, as well as past and personal medical history. Results: The findings of the current study indicate a significant increase in the risk of several complications among pregnant women with anaemia. These complications include pre-eclampsia, PTVD, PPH, puerperal sepsis, a higher caesarean section rate, eclampsia, placenta previa, abortion, and abruption. The study also encompasses non-pregnant patients ranging from menarche to menopause, highlighting an increased risk of dysmenorrhea, menorrhagia, puberty-related menorrhagia, ovarian cysts, and bleeding following medical termination of pregnancy (MTP) pills. Conclusions: Timely diagnosis and prompt intervention for anaemia can significantly decrease its prevalence. This initiative aims to foster a more health-conscious community.